Anticancer activity of liposomal formulation co-encapsulated with coumarin and phenyl butyric acid - Ali Allateef, Naeem Shalan, Zainab Lafi (Journal of Applied Pharmaceutical Science, 2024)
Anticancer treatments have poor pharmacokinetics, high toxicity to normal cells, and low bioavailability. As nanotechnology has advanced to a new level, many researchers have been motivated to develop a safer and more effective medication delivery method for the treatment of cancer. Nowadays, about 80% of the anticancer medications that have been approved recently are made from natural substances. This study aims to formulate liposomes loaded with coumarin (COM) and 4-phenylbutyric acid (PBA) and evaluate their antitumor effect in vitro. The liposomes were characterized using the dynamic light scattering instrument to determine their size, polydispersity, and charge. The formulated liposomes exhibited a particle size within the desired range of 100– 200 nm, with low polydispersity and suitable charge. Stability tests showed excellent stability of the liposomal formulations over 10 days in terms of size, charge, and polydispersity. High performance liquid chromatography analysis confirmed the successful encapsulation of COM and PBA within the liposomes, with high encapsulation efficiencies observed of 53%–25% for Lipo-PBA and Lipo-COM, respectively. Loading efficiency (LO%) was found to be 9%–5% for Lipo-PBA and Lipo-COM, respectively, which means the drugs were efficiently loaded within the liposome. In vitro cell viability studies demonstrated that the liposomes loaded with both COM and PBA exhibited the most effective inhibition on MDA-MB-231 breast cancer cells (30%) and A549 lung cancer cells (45%), while Lipo-COM showed potent inhibition on HT29 colorectal cancer cells (40%). Encapsulation of the drugs inside liposomes enhanced their cytotoxicity, potentially due to improved penetration into tumor cells. The findings suggest that the formulated liposomes have the potential for future clinical applications with high selectivity toward cancer cells.
Keywords: Liposomes, analytical methods, anticancer activity, HPLC method